Postural responses to specific types of long-term memory during visually induced roll self-motion. - Maëlle Tixier; Stéphane Rousset; Pierre-Alain Barraud; Corinne Cian (PLoS ONE)
A large body of research has shown that visually induced self-motion (vection) and cognitive processing may interfere with each other. The aim of this study was to assess the interactive effects of a visual motion inducing vection (uniform motion in roll) versus a visual motion without vection (non-uniform motion) and long-term memory processing using the characteristics of standing posture (quiet stance). As the level of interference may be related to the nature of the cognitive tasks used, we examined the effect of visual motion on a memory task which requires a spatial process (episodic recollection) versus a memory task which does not require this process (semantic comparisons). Results confirm data of the literature showing that compensatory postural response in the same direction as background motion. Repeatedly watching visual uniform motion or increasing the cognitive load with a memory task did not decrease postural deviations. Finally, participants were differentially controlling their balance according to the memory task but this difference was significant only in the vection condition and in the plane of background motion. Increased sway regularity (decreased entropy) combined with decreased postural stability (increase variance) during vection for the episodic task would indicate an ineffective postural control. The different interference of episodic and semantic memory on posture during visual motion is consistent with the involvement of spatial processes during episodic memory recollection. It can be suggested that spatial disorientation due to visual roll motion preferentially interferes with spatial cognitive tasks, as spatial tasks can draw on resources expended to control posture.